Labour, state and society in rural India : a class-relational approach - Pattenden, Jonathan (Manchester : Manchester University Press, 2016)
Drawing on fieldwork in rural South India over more than a decade, the book uses a 'class-relational' approach that focuses on 'the poor's' iniquitous relations with others.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 18, 2016).
Keywords: Rural poor -- India, South; India, South -- Rural conditions; Poverty -- India, South